Positive influence of simvastatin used as adjuvant agent for cavity lining - Leite, Maria Luísa [UNESP]; Soares, Diana Gabriela; de Oliveira Duque, Carla Caroline [UNESP]; Bordini, Ester Alves Ferreira [UNESP]; Anovazzi, Giovana [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2019)
Objectives: To assess the biological, antimicrobial, and mechanical effects of the treatment of deep dentin with simvastatin (SV) before application of a glass-ionomer cement (GIC). Materials and methods: Dentin discs were adapted to artificial pulp chambers and SV (2.5 or 1.0 mg/mL) was applied to the occlusal surface, either previously conditioned or not with EDTA (±EDTA). The extracts (culture medium + SV that diffused through dentin) was obtained and then applied to cultured odontoblast-like MDPC-23 cells. Cell viability, alkaline phosphatase (ALP) activity, and mineralization nodule (MN) deposition were evaluated. Untreated discs were used as control. The antibacterial activity of SV (2.5 or 1.0 mg/mL) against Streptococcus mutans and Lactobacillus acidophilus, as well as the bond strength of GIC to dentin in the presence of SV 2.5 mg/mL (±EDTA) were also assessed. The data were analyzed by ANOVA/Tukey tests (α = 5%). Results: EDTA + SV 2.5 mg/mL significantly enhanced the ALP activity and MN deposition in comparison with the control, without changing in the cell viability (p < 0.05). The association EDTA + SV 2.5 mg/mL + GIC determined the highest ALP and MN values (p < 0.05). SV presented intense antimicrobial activity, and the EDTA dentin conditioning followed by SV application increased bond strength values compared with SV treatment alone (p < 0.05). Conclusion: SV presents antimicrobial activity and diffuses across conditioned dentin to biostimulate odontoblast-like pulp cells. Clinical significance: The use of SV as adjuvant agent for indirect pulp capping may biostimulate pulp cells thus preserving vitality and function of the pulp-dentin complex.
Keywords: Antimicrobial activity; Biostimulation; Bond strength; Glass-ionomer cement; Pulp cells; Simvastatin